Foveal Avascular Zone Measurement Via Optical Coherence Tomography Angiography and its Relationship With the Visual Field in Eyes With Open-angle Glaucoma. Issue 6 (June 2020) - Igarashi, Ryoko; Ochiai, Shun; Togano, Tetsuya; Sakaue, Yuta; Suetake, Aki; Iikawa, Ryu; Honma, Yurie; Miyamoto, Daiki; Fukuchi, Takeo
Abstract : Precis: The foveal avascular zone (FAZ) in optical coherence tomography angiography is significantly correlated with retinal inner layer thickness, Humphrey field analyzer (HFA) 10-2 sensitivity threshold, and mean deviation (MD) value in open-angle glaucoma patients. Purpose: The purpose of this study was to measure the FAZ area using optical coherence tomography angiography and investigate its relationship with retinal inner layer thickness and visual field defects in eyes with open-angle glaucoma. Participants and Methods: A total of 52 eyes with open-angle glaucoma from 52 patients. FAZ area was measured using optical coherence tomography angiography in angio-macula mode. Thicknesses of retinal nerve fiber layer (RNFL), ganglion cell layer plus inner plexiform layer (GCL+IPL), and ganglion cell complex (GCC) were determined using a 7 mm×7 mm macular (V) map via 3D-OCT. Correlations of FAZ area with sensitivity threshold measurements, foveal threshold (FT), and MD value in the HFA10-2 visual field were analyzed for each inner retinal layer. Results: FAZ area was 0.26±0.07 mm 2 ; overall mean thicknesses were 19.14±6.55 μm (RNFL), 57.34±5.93 µm (GCL+IPL), and 75.87±10.96 μm (GCC); mean FT was 35.23±3.15 dB, and sensitivity threshold was 20.81±7.22 dB in the HFA10-2 visual field. FAZ area was significantly correlated with the thickness of individual retinal layers in the entire field (RNFL, P <0.001; GCL+IPL, P <0.001; GCC, P <0.001), sensitivity threshold ( P =0.01), FT ( P <0.001), and MD value ( P =0.011). Conclusion: FAZ area was significantly negatively correlated with retinal inner layer thickness, sensitivity threshold, FT, and MD value in the HFA10-2 visual field.